DESCRIPTIVE EPIDEMIOLOGY OF DIPHTHERIA CASES IN JEMBER REGENCY, INDONESIA, 2023–2024: Epidemiologi Deskriptif Kasus Difteri di Kabupaten Jember Tahun 2023-2024 - Khusnia, Esa Hidayatul; Noveyani, Adistha Eka; Ariyanto, Yunus (Universitas Airlangga, 2026)
Background: Diphtheria remains a significant public health concern in several regions of Indonesia, including Jember Regency, where periodic outbreaks persist. Purpose: This study aimed to describe the distribution of diphtheria cases in Jember Regency from 2023 to 2024 based on person, place, and time. Methods: A descriptive epidemiological study was conducted using secondary data from the Jember District Health Office, including all reported diphtheria cases from January 2023 to December 2024. The study population comprised all confirmed diphtheria cases during the study period, with data sources including case investigation forms, immunization records, and surveillance reports. Data were collected using a standardized extraction form and analyzed using descriptive statistics. Temporal trends were assessed through epidemic curves, while spatial distribution was mapped using Geographic Information System (GIS) software to visualize the relationship between immunization coverage and case occurrence. Results: A total of 27 diphtheria cases, or approximately 1.04 cases per 100,000 population, were reported. Most cases occurred among children aged 14 years or older, and clusters of cases were observed in subdistricts with low immunization coverage. The epidemic curve revealed distinct peaks in 2023 during weeks 23–27 and 28–31, while in 2024, peaks occurred during weeks 1–5 and 23–27. While GIS mapping demonstrated a clear spatial distribution between under-immunized areas and increased diphtheria incidence. Conclusion: Diphtheria cases were predominantly concentrated in areas with low immunization coverage, highlighting the need to strengthen immunization programs in vulnerable communities.